Navigating obstructive lingual thyroid coexisting with sub-clinical hypothyroidism: a case report - Maryam Ishaq; Muskan Hayat; Umar Fakhar; Wardah Zahoor; Israr Ud Din (Journal of the Pakistan Medical Association, 2025)
Ectopic thyroid tissue results from the embryonic failure of the thyroid gland to descend along the thyroglossal duct, resulting in the presence of thyroid tissue in an abnormal location. One of the most common locations where ectopic thyroid tissue (ETT) is found is at the base of the tongue, referred to as a lingual thyroid, having an estimated prevalence of 1 out of 100,000 to 300,000 in healthy individuals. We present the case of a 15-year-old female with a progressively enlarging mass at the base of her tongue, associated with dysphagia and sleep apnoea. Hormonal tests revealed hypothyroidism. Adopting a transoral approach, total resection was performed via electrocautery. Histopathology report revealed squamous lined tissue exhibiting mucous gland, confirming the diagnosis of ectopic lingual thyroid. The patient was started on thyroxine maintenance therapy and showed significant improvement. Keywords: Ectopic thyroid, lingual thyroid, hypothyroidism.